Trees and water: smallholder agroforestry on irrigated lands in Northern India - Zomer, Robert J.; Bossio, Deborah A.; Trabucco, Antonio; Yuanjie, Li; Gupta, Diwan C.; Singh, Virendra Pal (International Water Management Institute, 2007)
Trees are increasingly grown on-farm to supply wood and biomass needs within developing countries. Over the last several decades, within the irrigated rice-wheat growing lands of northern India, fast-growing poplar trees have been planted on tens of thousands of small farms. Recent debate regarding afforestation has raised the issue that water use is often increased when trees are planted. This ongoing debate focuses primarily on afforestation or reforestation of upland and rain-fed agricultural areas, and off-site impacts such as reduced streamflow. Adoption of poplar agroforestry in northern India, in contrast, is occurring in areas where land and water are already intensively used and managed for agricultural production. This study based on farmer survey data, used remote sensing and spatial hydrological modeling to investigate the importance and role of the poplar trees within the agricultural landscape, and to estimate their water use. Overall, results illustrate a potential for addressing the increasing global demand for wood products with trees grown on-farm within irrigated agroforestry systems.